OPTIMASI QUERY PADA LAPORAN TRANSAKSI PENJUALAN MENGGUNAKAN MATERIALIZED VIEW (Studi Kasus : Moonly café) - Febrianta Surya Nugraha; Febryan Hari Purwanto; Fachruddin Edi Nugroho Saputro (CCIT Journal, 2018)
The development of café business in Yogyakarta in 2017 is growing very rapidly. Moonly café currently uses sales information system using android platform and use data storage through cloud computing. The growing business café, transactions are done every day more and more. Sales information system runs slower when accessing larger data. These problems illustrate the lack of efficient time in data processing and the necessity of using query optimization in accessing data to speed up the process. The purpose of this study is to determine the speed performance in displaying monthly sales report by using query where clause, view table and materialized view table. The database is using MySql Server accessed via the internet, then recorded for the monthly sales report. In addition to comparing the performance of speed in displaying monthly sales reports, the authors also compare the speed of queries in displaying the report the amount of sales of each item each month on the table results of sales reports generated either from the query, view tables or materialized view tables. Use of materialized view to display monthly sales transaction reports faster than using query where clause or view. The use of materialized view to display reports the number of sales of each item each month faster than using the query where clause and view.